Aproximación a un modelo de despacho óptimo de flujo de agua en una red de acueducto - García Cáceres, Rafael Guillermo; López Castro, Mónica; Torres Mercado, José Fidel (Ingeniería, 2008)
This article presents a new formulation based in the better use of dynamic models in optimum planning and shipping. The specific case is the study of the water and sewerage system of Bogot. This model includes the analysis of the system; the act of supplying water from ponds to zones of service, allows taking decisions referent to eminently good volumes of water for periods of time in plants of treatment and better pumping time. In this order, the model helps to minimize the operation costs in the system. This formulation manage elements like: two-directional flows, the behavior of store deposits, the consumption of water in ponds, the piece-linear structure of costs, demands of water from hydraulic sectors, lower and upper levels of flow in the pipe line that conforms the water matrix network, and the capacity of plants of treatment, ponds, tanks and pumping stations.